Discrete time dynamic economic models : theory and empirical applications - Ferguson, Brian S. (Routledge, 2003)
Primarily of interest to upper level students carrying out economic modelling, this book bridges a gap between economics and econometric literature by introducing and developing the techniques of discrete time modelling.